ANÁLISE DA INFLUÊNCIA DA ESPESSURA DA CAVIDADE DE AR DE FACHADAS NATURALMENTE VENTILADAS NO SEU DESEMPENHO TÉRMICO - Souza, Leonardo; Souza, Henor; Rodrigues, Eliana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Ventilated façades consist in the construction of an external façade to the building so as to form a layer of circulating air and have been widely used throughout the world contributing to the thermal performance of the built environment. In this work, a study of the efficiency of a ventilated façade using a prototype cell, focusing on the airflow and the convection of heat in the cavity formed by the ventilated façade, is carried out. The study covers measurements in loco and numerical simulation. The cavity formed by façade, that is, the thickness of the air layer between the external façade and the external wall has its values varied by 20, 15 and 10 cm. ANSYS CFX software implements a numerical model to evaluate the convection of heat in the cavity and the airflow. The results show that the presence of the ventilated façade contributes to a decrease of the temperature inside the environment and the thickness of the cavity plays an important role so that it varies the speed of wind in the entry and the heat exchange between the faces of the walls.